Предмет: Алгебра,
автор: skarletwolberk
Замени d одночленом так, чтобы получился квадрат бинома
16z^2−5z+d
Ответы
Автор ответа:
0
16z² - 5z + d = (4z)² - 5z + d
5z = 2 * 4z * x
5z = 8 * z * x
x = 5z / 8z
x = 5 / 8
Тогда d = x² = 25 / 64
16z^2 − 5z + 25 / 64 = (4z - 5/8)²
5z = 2 * 4z * x
5z = 8 * z * x
x = 5z / 8z
x = 5 / 8
Тогда d = x² = 25 / 64
16z^2 − 5z + 25 / 64 = (4z - 5/8)²
Похожие вопросы
Предмет: Русский язык,
автор: fyfsgdhsdft6
Предмет: Английский язык,
автор: tanfut
Предмет: Русский язык,
автор: Newknowledge
Предмет: Математика,
автор: elizavetaf200510
Предмет: Математика,
автор: mila12525